DEVELOPMENT AND QUALITY ASSESSMENT OF BREAD PREPARED BY USING WHEAT FLOUR, ALMOND FLOUR AND INULIN POWDER - Abhishek Gautam 1, Shanker Suwan Singh 2, Pooja Yadav 3, Dudekula Prudhvi 4 (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This research highlights the potential of using almond and inulin powders to produce a more Nutritious bread product, offering a valuable alternative to conventional bread formulations. The Findings contribute to the growing body of knowledge on functional ingredients in baked goods And provide a foundation for future studies on the health benefits and market potential of enhanced bread products. This Research investigates the formulation and quality evaluation of bread incorporating wheat flour, almond powder, and inulin powder.